A multi-objective approach to the prospective development of the European power system by 2050. (15th January 2020) - Louis, Jean-Nicolas; Allard, Stéphane; Kotrotsou, Freideriki; Debusschere, Vincent
Abstract: This paper reports the recent work carried out to engage both the environmental impact and the economic indicators on the prioritisation of dispatchable technologies in the European energy mix up to 2050. Those two contradictory indicators are incorporated in a multi-criteria optimisation leading to iterations of two scenario: business as usual and 2 °C climate policy. The results present the evolution of the climate change emission versus the operational costs of the power system up to 2050. The yearly electricity mix evaluations allow assessing the long-term development of the European energy system, where a focus is done on variable renewable energy production. It is shown that policy-only solutions, associated with a traditional cost-oriented optimisation, have a limited impact on helping the power sector to reach emission levels targets. Integrating the objective of reducing emissions to the management of power plants would reduce the absolute and cumulative carbon dioxide equivalent emissions. The counterpart is that the system electricity price tends to increase faster thus implying increased social costs. Graphical abstract: Image 1 Highlights: Transmission grid and dispatch model using life cycle assessment indicators. Multi-objective assessment of the European power system development by 2050. Policy-only solutions have a limited impact on reaching targets level. System costs optimisation favours inter-cluster power exchange. Emission optimisation favours technology shift and decrease power exchange.